Neuroglial Senescence, α-Synucleinopathy, and the Therapeutic Potential of Senolytics in Parkinson’s Disease - Miller, Sean J.; Campbell, Cameron E.; Jimenez-Corea, Helen A.; Wu, Guan-Hui; Logan, Robert (Frontiers in Neuroscience, 2022)
Parkinson’s disease (PD) is the most common movement disorder and the second most prevalent neurodegenerative disease after Alzheimer’s disease. Despite decades of research, there is still no cure for PD and the complicated intricacies of the pathology are still being worked out. Much of the research on PD has focused on neurons, since the disease is characterized by neurodegeneration. However, neuroglia have become recognized as key players in the health and disease of the central nervous system. This review provides a current perspective on the interactive roles that α-synuclein and neuroglial senescence have in PD. The self-amplifying and cyclical nature of oxidative stress, neuroinflammation, α-synucleinopathy, neuroglial senescence, neuroglial chronic activation and neurodegeneration will be discussed. Finally, the compelling role that senolytics could play as a therapeutic avenue for PD is explored and encouraged.